Cystic fibrosis-related liver disease: a single-center experience - Paula Catarino Costa; Celeste Canha Barreto; Luisa Pereira; Maria Luisa Lobo; Maria Adília Costa; Ana Isabel Gouveia Lopes (MDPI AG, 2011)
Prospective studies concerning liver disease in pediatric cystic fibrosis patients are scarce. The present study aimed to describe the prevalence and clinical expression of cystic fibrosis - related liver disease, in a cohort of 62 pediatric patients. Descriptive study, resulting from the prospective evaluation, between 1994 and 2009, of 62 pediatric patients (age <18 years) with cystic fibrosis. The follow-up protocol included a clinical assessment every 2 months, liver function tests every 6 months and annual liver ultrasonography. The cumulative prevalence of liver disease was 11.2% (7/62 cases). All patients had ΔF508 mutation and pancreatic insufficiency, none had meconium ileus. The liver involvement became clinically evident at a mean age of 8 years (3-15 years), revealed by hepatomegaly or hepatosplenomegaly (3 cases) and/ or abnormalities of liver function tests (3 cases) changes of liver ultrasound (7 cases) with evidence of portal hypertension (2 cases). Four patients were submitted to liver biopsy; biliary fibrosis was documented in one case, focal biliary cirrhosis in 2 cases and multilobular cirrhosis in another case. Within a median 11.6 years follow-up period (all patients under UDCA therapy after liver disease diagnosis), progression of liver disease was observed in 2 patients; one patient developed refractory variceal bleeding and progressive hepatic failure, requiring liver transplant. The results of the present study agree with those of previous pediatric studies, further documenting clinical expression of liver disease in CF patients, which is usually detected in the first decade of life and emphasize the contribution of ultrasound to early diagnosis of liver involvement. Moreover, although advanced liver disease is a relatively rare event, early isolated liver transplantation may have to be considered at this age group.